Pengaruh Modifikasi Media Tanam Hidroton dan Zat Pengatur Tumbuh terhadap Produktivitas Tanaman Pakcoy (Brassica rapa L.) Secara Hidroponik Sistem Wick - Nabila, Nila Anjali; Purbajanti, Endang Dwi; Budiyanto, Susilo (JURNAL AGROTROPIKA, 2024)
The quality of pakcoy plants in hydroponic cultivation is influenced by the planting medium and the growth regulators given to the leaves of pakcoy plants to get good plant results. The aim of the research was to examine the effect of modifying hydroton planting media by providing plant growth substances concentrations on plant growth and production. This research uses 3 x 4 Factorial Complately Random Design with 3 replications. The first factor for modification of hydroton planting media includes hydroton (M0), hydroton+cocopeat (M1), hydroton+charcoal husk (M2), the second factor PGR concentration includes o ml/liter (H0), 2 ml/liter (H1), 4 ml /liter (H2), 6ml/liter (H3). Data were analyzed using Range Analysis and tested further using DMRT (Duncan Multiple Range Test) at the 5% level. The research results showed that there was an interaction effect between modified hydroton planting media and PGR concentration on leaf width and leaf area parameters. The hydroton planting media modification treatment had a significant effect on all parameters except root length.  Keywords : cocopeat, hidroton, modification, pakcoy